Unidirectional versus bidirectional brushing: Simulating wind influence on Arabidopsis thaliana. (11th April 2022) - Zhdanov, Oleksandr; Blatt, Michael R.; Zare-Behtash, Hossein; Busse, Angela
Abstract: Abstract: Plants acclimate to various types of mechanical stresses through thigmomorphogenesis and alterations in their mechanical properties. Although resemblance between wind- and touch-induced responses provides the foundation for studies where wind influence was mimicked by mechanical perturbations, factorial experiments revealed that it is not always straightforward to extrapolate results induced by one type of perturbation to the other. To investigate whether wind-induced changes in morphological and biomechanical traits can be reproduced, we subjected Arabidopsis thaliana to two vectorial brushing treatments. Both treatments significantly affected the length, mechanical properties and anatomical tissue composition of the primary inflorescence stem. While some of the morphological changes were found to be in line with those induced by wind, changes in the mechanical properties exhibited opposite trends irrespective of the brushing direction. Overall, a careful design of the brushing treatment gives the possibility to obtain a closer match to wind-induced changes, including a positive tropic response.